2015
DOI: 10.1007/s00231-015-1615-2
|View full text |Cite
|
Sign up to set email alerts
|

Performance enhancement of an experimental air conditioning system by using TiO2/methanol nanofluid in heat pipe heat exchangers

Abstract: Specific enthalpy of desired conditioned air (at 18 °C and 55 % RH) HPHX Heat pipe heat exchanger HVAC Heating, ventilation, and air conditioninġ m Mass flow rate of air passing through the condenseṙ m min Minimum of mass flow rates between air streams in pre-cooling and reheating sections q act Actual heat transfer rate q max Maximum heat transfer rate RH Relative humidity RH e,i Relative humidity of inlet air to the HPHX evaporator S e Energy saving in evaporator section S c Energy saving in condenser sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Based on a comprehensive consideration of the main purpose of supplying the energy required for reheating, they suggested that 2 wt.% TiO 2 –methanol nanofluid for the four-row HPHX would have been adequate and more economical.
Fig. 10Schematic of the experimental apparatus [115]. Reproduced with permission from Springer
…”
Section: Heat Pipesmentioning
confidence: 99%
“…Based on a comprehensive consideration of the main purpose of supplying the energy required for reheating, they suggested that 2 wt.% TiO 2 –methanol nanofluid for the four-row HPHX would have been adequate and more economical.
Fig. 10Schematic of the experimental apparatus [115]. Reproduced with permission from Springer
…”
Section: Heat Pipesmentioning
confidence: 99%
“…Thereafter, it is dispersed in the base fluids. Monirimanesh (2016) gives the agglomeration is high in this method, because of its prolonged stages in the preparation.…”
Section: Preparation Of Nanofluidsmentioning
confidence: 97%
“…The two methods are used to prepare the Nano fluids are single-step method and two-step method. For the preparation of SiO 2 and TiO 2 particles, two-step method is more suitable from Monirimanesh (2016). In the two step method, initially nano-scale sized metals, metal oxides, fiber particles and carbon nanotubes (CNT/NCT) are prepared.…”
Section: Preparation Of Nanofluidsmentioning
confidence: 99%
“…Then the dry powder is produced by various processes like chemical vapor condensation, mechanical alloying, etc. Thereafter, it is dispersed in the base fluids from Negin Monirimanesh [2]. The agglomeration is high in this method, because of its The evaporator section was heated by a nichrome coil surrounding at its circumference and the power supply to the Nichrome coil was given by auto transformer.…”
Section: Preparation Of Nanofluidsmentioning
confidence: 99%
“…In the two scale sized metals, metal oxides, fiber particles and carbon nanotubes e dry powder is produced by various processes like chemical vapor condensation, mechanical alloying, etc. Thereafter, it is dispersed in the base fluids from Negin Monirimanesh [2]. The agglomeration is high in this method, because of its prolonged stages in the preparation.…”
Section: Preparation Of Nanofluidsmentioning
confidence: 99%